2017
DOI: 10.1007/s00384-017-2892-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety of endoscopic mucosal resection (EMR) of large non-pedunculated colorectal adenomas in the elderly

Abstract: BackgroundEndoscopic mucosal resection (EMR) has been proven to be safe and effective for the treatment of colorectal adenomas. However, data are limited on the safety of this technique for large polyps and in elderly patients. Aims of our study were to examine the bleeding and perforation rates in patients with large non-pedunculated adenomas (≥20mm) and to evaluate the influence of size (≥40mm) and age (≥75 years) on the complication rates.MethodsIn this multicenter retrospective study, patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
(39 reference statements)
1
22
0
Order By: Relevance
“…Focusing on postprocedural bleeding, rates ranging from 2.2% to 6.7% have been reported in the literature when using hot EMR for large polyps. 22,23 In our pooled analysis the postprocedural bleed rate was .5% for all polyps !10 mm and 0% when the analysis was restricted just to studies on EMR. Although randomized controlled trials would be required, if we do compare these results with previous meta-analyses on conventional polypectomy or EMR techniques, [24][25][26] CSP appears to be substantially safer.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Focusing on postprocedural bleeding, rates ranging from 2.2% to 6.7% have been reported in the literature when using hot EMR for large polyps. 22,23 In our pooled analysis the postprocedural bleed rate was .5% for all polyps !10 mm and 0% when the analysis was restricted just to studies on EMR. Although randomized controlled trials would be required, if we do compare these results with previous meta-analyses on conventional polypectomy or EMR techniques, [24][25][26] CSP appears to be substantially safer.…”
Section: Discussionmentioning
confidence: 69%
“…25 The overall residual polyp rate for our study was 4.7% after cold EMR for polyps !10 mm, lower than the reported numbers in the literature. Focusing on lesions !20 mm, Bronsgeest et al 22 showed a recurrence rate of 18.8% after conventional EMR. In our pooled analysis the recurrence rate for polyps !20 mm was 15.4%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since 2012, only one patient undergoing UEMR developed perforations, as described previously [ 27 ]. However, in a report on CEMR, the perforation rate ranged from 1.2 to 4.4% in patients who underwent CEMR [ 28 , 29 ]. These previous findings further confirm the safety of UEMR.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, colorectal surgery involves a significant risk of morbidity (30%) and even mortality (1%-5%), especially in the elderly population, [10][11][12] the main target group of screening programs. 13,14 On the contrary, therapeutic colonoscopies, including endoscopic resection of large colon polyps, 15,16 carry a low risk of morbidity and mortality and are therefore considered to be safe in the elderly. 17 Because an accurate weighing up of oncologic benefit versus the risk of treatmentrelated adverse events remains challenging, eliciting the patient's perspective becomes especially important.…”
mentioning
confidence: 99%